Capturing Interiority - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (UI Scholars Hub, 2023)
The idea of interiority is manifested in various forms, emerging through subjective modes of engaging with space and place, personal experiences, and ways of seeing. Simultaneously, interiority is also manifested in physical entities that act as traces of inhabitation. This issue of Interiority presents a collection of inquiries that attempt to capture the traces of interiority in different everyday contexts using various modes of inquiry and representational media. They demonstrate how the idea of interiority could be captured through everyday images, the presence of objects in space, locality narratives, and spatial arrangements of inhabited space.